Energy and Emission Analysis of Residential Sector: A Case Study for Reshunga Municipality in Nepal - Panthi, Biswambhar; Bhattarai, Nawraj (Journal of Advanced College of Engineering and Management, 2018)
This paper presents energy consumption in a municipality within hilly region and also analyzes GHG emission under different scenario. For the purpose of study Reshunga municipality was taken, situated in Gulmi district of Nepal occupying an area of 82.74 sq.km. For collection of data, 368 houses were surveyed and the locals were interviewed on their annual consumption. The total energy consumption was 214.8 TJ where 78.25% was supplied by wood. LPG shared 16.14% of demand. Cooking (58%) and water boiling (26%) were the most demanding task. Most of the houses were equipped with ICS, with share 55% of energy demand in cooking. Four different scenario were studied viz. BAU, DSM, BSP and SDG. In, BAU scenario, the energy consumption will reach 245.3 TJ. In DSM scenario and BSP scenario the final energy demand will reduce to 230.7 TJ and 216.2 TJ. In SDG scenario, energy demand is reduced by 23.14%. The share of LPG increases to 22.36 % and electricity demand becomes more than doubles from reaching 10.64% in SDG. From year 2017-2030, there will be total accumulative increase of electricity requirement by 47.4 TJ, whereas total cumulative decrease of 433.5 TJ equivalents can be resulted in consumption of wood in SDG scenario. Cost-Benefit analysis study revealed that DSM will require an investment of 43.03K US$ for demand technologies and will reduce emission by 8.69 tCO2e. DSM will be cheapest in terms of cost per GHG reduction. SDG will cost 645.46K US$ and results in reduction of GHG by 47.79K tCO2e.